OGDA: a comprehensive organelle genome database for algae. (28th November 2020) - Liu, Tao; Cui, Yutong; Jia, Xuli; Zhang, Jing; Li, Ruoran; Yu, Yahui; Jia, Shangang; Qu, Jiangyong; Wang, Xumin
Abstract: Algae are the oldest taxa on Earth, with an evolutionary relationship that spans prokaryotes (Cyanobacteria) and eukaryotes. A long evolutionary history has led to high algal diversity. Their organelle DNAs are characterized by uniparental inheritance and a compact genome structure compared with nuclear genomes; thus, they are efficient molecular tools for the analysis of gene structure, genome structure, organelle function and evolution. However, an integrated organelle genome database for algae, which could enable users to both examine and use relevant data, has not previously been developed. Therefore, to provide an organelle genome platform for algae, we have developed a user-friendly database named Organelle Genome Database for Algae (OGDA, http://ogda.ytu.edu.cn/ ). OGDA contains organelle genome data either retrieved from several public databases or sequenced in our laboratory (Laboratory of Genetics and Breeding of Marine Organism [MOGBL]), which are continuously updated. The first release of OGDA contains 1055 plastid genomes and 755 mitochondrial genomes. Additionally, a variety of applications have been integrated into this platform to analyze the structural characteristics, collinearity and phylogeny of organellar genomes for algae. This database represents a useful tool for users, enabling the rapid retrieval and analysis of information related to organellar genomes for biological discovery.